2013
DOI: 10.2140/agt.2013.13.1579
|View full text |Cite
|
Sign up to set email alerts
|

Some Ramsey-type results on intrinsic linking ofn–complexes

Abstract: Define the complete n-complex on N vertices, K n N , to be the n-skeleton of an (N − 1)-simplex. We show that embeddings of sufficiently large complete n-complexes in R 2n+1 necessarily exhibit complicated linking behaviour, thereby extending known results on embeddings of large complete graphs in R 3 (the case n = 1) to higher dimensions. In particular, we prove the existence of links of the following types: r-component links, with the linking pattern of a chain, necklace or keyring; 2-component links with li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The proposition plays the role of Flapan, Mellor and Naimi's Lemma 2, and the statement and proof are heavily modelled on theirs, making modifications as needed for it to work in all dimensions and achieve the divisibility condition. From an arithmetic standpoint, realising the divisibility condition largely boils down to repeatedly applying the following simple number-theoretic observation, used by both Fleming [5] and Tuffley [10]:…”
Section: 2mentioning
confidence: 99%
See 4 more Smart Citations
“…The proposition plays the role of Flapan, Mellor and Naimi's Lemma 2, and the statement and proof are heavily modelled on theirs, making modifications as needed for it to work in all dimensions and achieve the divisibility condition. From an arithmetic standpoint, realising the divisibility condition largely boils down to repeatedly applying the following simple number-theoretic observation, used by both Fleming [5] and Tuffley [10]:…”
Section: 2mentioning
confidence: 99%
“…The result is a disc D n , and the triangulation D n = ∆ 1 ∪ · · · ∪ ∆ ℓ satisfies Definition 2.2 by construction. In Lemma 2.6 of [10] it is shown that a disc constructed in this way has ℓ + n vertices, and the number of (n − 1)-simplices in ∂D n is ℓ(n − 1) + 2. We note that for n ≥ 2 a path does not necessarily have this form: for instance, for n = 2 the triangulation of a regular n-gon by radii may be given the structure of a path.…”
Section: Constructing Links With Large Componentsmentioning
confidence: 99%
See 3 more Smart Citations